2003
DOI: 10.1074/jbc.m302134200
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hepatic Fructose 2,6-Bisphosphate after an Oral Glucose Load Does Not Affect Gluconeogenesis

Abstract: The generally accepted metabolic concept that fructose 2,6-bisphosphate (Fru-2,6-P 2 ) inhibits gluconeogenesis by directly inhibiting fructose 1,6-bisphosphatase is based entirely on in vitro observations. To establish whether gluconeogenesis is indeed inhibited by Fru-2,6-P 2 in intact animals, a novel NMR method was developed using [U-13 C]glucose and 2 H 2 O as tracers. The method was used to estimate the sources of plasma glucose from gastric absorption of oral [U-13 C]glucose, from gluconeogenesis, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
5
23
0
Order By: Relevance
“…[7,15]) and hyperglycemia [13], whereas gluconeogenesis remains nearly the same [15]. A recent study on the effects of oral glucose load showed no acute changes in gluconeogenesis [16], which is consistent with the above observations. Thus, it is important to note that gluconeogenesis remains roughly constant during the fasted to fed transition, e.g., a period of 180 ~ 240 minutes.…”
Section: Glucose Homeostasis and Hepatic Glucose Fluxsupporting
confidence: 76%
See 1 more Smart Citation
“…[7,15]) and hyperglycemia [13], whereas gluconeogenesis remains nearly the same [15]. A recent study on the effects of oral glucose load showed no acute changes in gluconeogenesis [16], which is consistent with the above observations. Thus, it is important to note that gluconeogenesis remains roughly constant during the fasted to fed transition, e.g., a period of 180 ~ 240 minutes.…”
Section: Glucose Homeostasis and Hepatic Glucose Fluxsupporting
confidence: 76%
“…These states are classically thought to be able to inhibit gluconeogenesis [61]. This result was further confirmed by an NMR study, directly investigating hepatic gluconeogenesis, which showed that gluconeogenesis is not changed under the high F-2,6-P 2 state [16]. Thus, FBPase is not inhibited by F-2,6-P 2 in vivo, as it has been shown to be in vitro, indicating a limited role for FBPase in contributing to a lowering of HGP, at least in the acute nutritional transition phase.…”
Section: Therapeutic Targets For Reduction Of Hepatic Glucose Productionsupporting
confidence: 75%
“…Since cellular function is not only modulated by autonomous programs but also by microenvironmental stimuli (neighbor cells, extracellular matrix, soluble factors, and physical forces), regulation of activity and subcellular distribution of enzymes in the multicellular context of the tissue is poorly understood yet. Moreover, differences have been demonstrated when comparing whole organ with in vitro experiments [Jin et al, 2003;Matsuo et al, 2010]. Here, we present evidence that the regulation of FBPase nucleo-cytoplasmic shuttling is impaired during diabetes, whereas the liver zonation was not affected.…”
mentioning
confidence: 46%
“…Previously, the in vivo effects of F26P 2 on inhibition of the flux through gluconeogenic pathway have not been established, although F26P 2 has been identified as an inhibitor of the gluconeogenic enzyme FBPase for over 25 years (20). In fact, there was evidence to the contrary where Jin et al (8) showed that high levels of F26P 2 did not suppress gluconeogenesis in rats after an oral glucose load. Here, the present data are the first to demonstrate that low levels of F26P 2 lead to an increase in gluconeogenesis in vivo.…”
Section: Discussionmentioning
confidence: 81%